Public subsidies for private schools: The politics of financing private schools in Australia and Switzerland - Nikolai, Rita (Swiss Journal of Educational Research, 2019)
The article analyses the politics of subsidies for private schools in Australia and Switzerland. Based on the analyses of primary and secondary sources, this article adopts a historical-institutionalist perspective for examining the role of political parties, teacher unions and other interest groups as well as their strategies in subsidizing private schools. In Australia, private schools have gained a broad support of the different political camps since the 1970s and due to generous public subsidies private schools could expand. In contrast, Swiss school politics is characterized by considerable reluctance towards subsidizing private schools.